Answer: c 14m
Step-by-step explanation: hope this helped
Answer:
10 will be answer
Step-by-step explanation:
hoh(x) = x
Answer:
Step-by-step explanation:
Depending on whether or not the g(x) is x^2 or 2x, I have both ways.
If g(x) is x^2 - 9...
--> (3x^2 + 2) - (x^2 - 9) = 2x^2 + 11
If g(x) is 2x...
--> (3x^2 + 2) - (2x - 9) = 3x^2 - 2x + 11
Hope this helps!
Answer:
a) 13 m/s
b) (15 + h) m/s
c) 15 m/s
Step-by-step explanation:
if the location is
y=x²+3*x
then the average velocity from 3 to 7 is
Δy/Δx=[y(7)-y(3)]/(7-3)=[7²+3*7- (3²+3*3)]/4= 13 m/s
then the average velocity from x=6 to to x=6+h
Δy/Δx=[y(6+h)-y(6)]/(6+h-6)=[(6+h)²+3*(6+h)- (6²+3*6)]/h= (2*6*h+3*h+h²)/h=2*6+3= (15 + h) m/s
the instantaneous velocity can be found taking the limit of Δy/Δx when h→0. Then
when h→0 , limit Δy/Δx= (15 + h) m/s = 15 m/s
then v= 15 m/s
also can be found taking the derivative of y in x=6
v=dy/dx=2*x+3
for x=6
v=dy/dx=2*6+3 = 12+3=15 m/s
Across the large angle is going to be large side, then AB is going to be larger than DF.